2003
DOI: 10.1084/jem.20021109
|View full text |Cite
|
Sign up to set email alerts
|

Vaginal Submucosal Dendritic Cells, but Not Langerhans Cells, Induce Protective Th1 Responses to Herpes Simplex Virus-2

Abstract: Herpes simplex virus (HSV) type 2 infection occurs primarily at the genital mucosal surfaces and is a leading cause of ulcerative lesions. Despite the availability of animal models for HSV-2 infection, little is known regarding the mechanism of immune induction within the vaginal mucosa. Here, we examined the cell types responsible for the initiation of protective Th1 immunity to HSV-2. Intravaginal inoculation of HSV-2 led to a rapid recruitment of submucosal dendritic cells (DCs) to the infected epithelium. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

15
405
1
2

Year Published

2006
2006
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 354 publications
(423 citation statements)
references
References 35 publications
15
405
1
2
Order By: Relevance
“…Also consistent with immunoregulation, the TLR expression profile by LC with low expression of TLR-2 and -4 necessary for bacterial recognition results in selective unresponsiveness of LC to bacteria compared with viruses and may contribute to tolerance to bacterial commensals [8,9]. In some cases dermal DC may play the immunostimulatory role previously attributed to LC [10][11][12]. Recently, a distinct subset of dermal DC was identified in mouse that expresses langerin and this subset might be important for immunostimulation [13][14][15] although so far, little is known about their function and whether a similar subset exists in humans.…”
Section: Biology Of Lc and Interactions With Virusesmentioning
confidence: 67%
See 1 more Smart Citation
“…Also consistent with immunoregulation, the TLR expression profile by LC with low expression of TLR-2 and -4 necessary for bacterial recognition results in selective unresponsiveness of LC to bacteria compared with viruses and may contribute to tolerance to bacterial commensals [8,9]. In some cases dermal DC may play the immunostimulatory role previously attributed to LC [10][11][12]. Recently, a distinct subset of dermal DC was identified in mouse that expresses langerin and this subset might be important for immunostimulation [13][14][15] although so far, little is known about their function and whether a similar subset exists in humans.…”
Section: Biology Of Lc and Interactions With Virusesmentioning
confidence: 67%
“…However, others and we have recently shown that LC are not the cells presenting HSV antigen to CD8 1 T cells in lymph nodes. After epidermal scarification with the virus, it was observed that CD8 1 DC present HSV antigens to CD8 1 T cells in draining lymph nodes 24 h after infection [57], and after vaginal inoculation of HSV, dermal DC were demonstrated to present HSV antigen to CD4 1 T cells [12]. The apparent paradox of initial HSV antigen uptake by LC but presentation by another DC subtype may be explained by transfer of the antigens from one DC subtype to another [57].…”
mentioning
confidence: 99%
“…It was recently reported that the migration of dermal DCs to dCLNs takes slightly more than 90 min, whereas LC migration can take more than 24 h [8]. Therefore, to evaluate the role of migrating skin DCs in antigen presentation, we removed the ear 90 min after HEL inoculation.…”
Section: Resultsmentioning
confidence: 99%
“…Although Langerhans cells (LCs) have been shown to be potent APCs in vitro [3], in vivo approaches have produced conflicting data regarding their role in T-cell priming [4,5]. Dermal DCs are also migrating DCs that colonize lymph nodes more rapidly than LCs [6,7], and different roles for skin DC subsets in T-cell priming have been reported [7][8][9]. Skin immunization has yielded controversial data, with some reports supporting a Th2-type response [10,11] and others a Th1-type response [12,13].…”
mentioning
confidence: 99%
See 1 more Smart Citation